Dataset on human rights awareness in Northwest Nigeria - Kasim Balarabe (Elsevier, 2021)
The data in this article investigated the extent of human rights awareness in the seven States comprising the Northwest geopolitical zone of Nigeria and its relationship with the characteristics of the population in the light of limited human rights claims in the region. The data was obtained from 780 respondents using stratified and systematic random sampling techniques using with the help of a structured questionnaire. It is aimed at ascertaining, among others, the extent to which the population in the region is aware of human rights and the meaning of the terms ‘marginalisation' and ‘discrimination', whether the population is aware of how to claim human rights and whether the population is comfortable approaching the courts for human rights claims. The questionnaire also sought information on the most utilised sources of information, formal and informal factors that influence a decision to litigate human rights violations, and the most common complaint mechanisms employed by the population concerning human rights violations. The responses were analysed using Qualtrics software, and the data was presented using statistical representations. The data shows an appreciable level of human rights understanding in the region.